2021
DOI: 10.1111/jocn.16162
|View full text |Cite
|
Sign up to set email alerts
|

Towards patient‐centred communication in the management of older patients' medications across transitions of care: A focused ethnographic study

Abstract: Background Communication about managing medications during transitions of care can be a challenging process for older patients since they often have complex medication regimens. Previous studies highlighted that links between communication breakdowns and medication incidents in older patients occur mainly at discharge or in the post‐discharge period. Little attention has been paid to exploring communication strategies facilitating patient‐centred medication communication at transitions of care from a discourse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 57 publications
3
9
2
Order By: Relevance
“…The discharge context in acute care wards may entrench patient passivity. 14 Older patients report more satisfaction when discharge medication information is given in an environment of 'peace' and 'quiet' 37 , which was inconsistent with the noisy environments in our study. On the other hand, patient-related factors may have influenced passivity.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The discharge context in acute care wards may entrench patient passivity. 14 Older patients report more satisfaction when discharge medication information is given in an environment of 'peace' and 'quiet' 37 , which was inconsistent with the noisy environments in our study. On the other hand, patient-related factors may have influenced passivity.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, conversations tended to be monologues and conversation topics were overwhelming initiated by healthcare professionals; yet, our study showed the almost 70% of patients preferred an active role, thus it is not clear why patients were so passive? The discharge context in acute care wards may entrench patient passivity 14. Older patients report more satisfaction when discharge medication information is given in an environment of ‘peace’ and ‘quiet’37, which was inconsistent with the noisy environments in our study.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations